2010
DOI: 10.1016/j.jweia.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Wind tunnel tests on train scale models to investigate the effect of infrastructure scenario

Abstract: Abstract. The cross wind risk analysis is today, within the European railway operators, one of the most important items related to the safety problem. In order to define the risk associated to the cross wind along a railway line, the effects of the infrastructure scenarios on the aerodynamic loads acting on a vehicle have to be investigated. A typical railway line is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(72 citation statements)
references
References 5 publications
0
72
0
Order By: Relevance
“…Therefore, it is important to study the effects of different road conditions on the aerodynamic performance of the train to determine the aerodynamic performance and safety of the vehicle [8] . Trains are affected by aerodynamic loads when traveling on viaducts, embankments, and other infrastructure structures (Cheli et al 2010a) [9] . The aerodynamic forces of trains running on typical structures such as embankments and viaducts are investigated by wind tunnel tests (Suzuki et al, 2003;Bocciolone et al, 2008) [10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to study the effects of different road conditions on the aerodynamic performance of the train to determine the aerodynamic performance and safety of the vehicle [8] . Trains are affected by aerodynamic loads when traveling on viaducts, embankments, and other infrastructure structures (Cheli et al 2010a) [9] . The aerodynamic forces of trains running on typical structures such as embankments and viaducts are investigated by wind tunnel tests (Suzuki et al, 2003;Bocciolone et al, 2008) [10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…In the literature of specialty [8], [9], [10], [11], [12], [13], [14], [15], the explanation of the "c", parameter corresponding to the determination of the drag, given by the aerodynamic phenomena, from Davis' equation for rail vehicles moving at speeds up to 250 km / h, in the longitudinal direction is expressed in the form given by relation (2): In the article "Aerodynamics of high-speed railway train" [16] the authors state that in a series of tests made in a "test tunnel" on TGV trains at a speed of 260 km/h they found that "Of the total aerodynamic drag, about 80% is given only by the body train aerodynamics, 17% of aerodynamics is due to the pantograph system and other devices on the train and the remaining 3% is caused by the braking mechanisms, etc. "…”
Section: Introductionmentioning
confidence: 99%
“…The crosswind stability against overturning is a major design criterion for high speed railway vehicles and has been an experimental and/or numerical research topic for a number of scholars [15][16][17][18][19][20][21][22]. The experimental study allows to have a higher confidence in the absolute values of the measured aerodynamic forces where the numerical calculations allow to obtain a more detailed information of the flow field around the vehicle.…”
mentioning
confidence: 99%